Exercise alters SIRT1, SIRT6, NAD and NAMPT levels in skeletal muscle of aged rats - Koltai, Erika (2009)
Silent information regulators are potent NAD(+)-dependent protein deacetylases, which have been shown to regulate gene silencing, muscle differentiation and DNA damage repair. Here, changes in the level and activity of sirtuin 1 (SIRT1) in response to exercise in groups of young and old rats were studied. There was an age-related increase in SIRT1 level, while exercise training significantly increased the relative activity of SIRT1. A strong inverse correlation was found between the nuclear activity of SIRT1 and the level of acetylated proteins. Exercise training induced SIRT1 activity due to the positive effect of exercise on the activity of nicotinamide phosphoribosyltransferase (NAMPT) and thereby the production of sirtuin-fueling NAD(+). Exercise training normalized the age-associated shift in redox balance, since exercised animals had significantly lower levels of carbonylated proteins, expression of hypoxia-inducible factor-1alpha and vascular endothelial growth factor. The age-associated increase in the level of SIRT6 was attenuated by exercise training. On the other hand, aging did not significantly increase the level of DNA damage, which was in line with the activity of 8-oxoguanine DNA glycosylase, while exercise training increased the level of this enzyme. Regular exercise decelerates the deleterious effects of the aging process via SIRT1-dependent pathways through the stimulation of NAD(+) biosynthesis by NAMPT.